Cholecystokinin action on the lateral parabrachial nucleus to inhibit salt appetite - Menani, J. V. [UNESP]; Johnson, A. K. [UNESP] (My University, 1996)
In the present study we Investigated the effect of bilateral injection of ptoglumide (cholecystolcinin receptor antagonist) or cholecystokinin(CCK-8) into the lateral parabrachial nucleus (LPBN) on the ingestion of 0.3 M NaCl and water induced by angiotensin II (ANG IDicv or combined treatment with subcutaneous (sc) furosemide (FURO) + captopril 4CAP). Rats were implanted with bilateral stainless steel cannulas in the LPBN and one cannula in the lateral ventricle. Bilateral LPBN injection of proglumide (50 ug/0.2 ul) increased the ingestion of 0.3 M NaCl (10.113.2 vs 1.3±0.3 ml in 1 h, n-15) but not water (16.9±2.4 vs 12.3±1.1 ml) induced by icv ANG II (50 ng/1 μl). The Ingestion of 0.3 M NaCl (17.9±3.8 vs 5.610.8 ml in 2 h, n-9) and water (16.212.0 vs 8.110.9 ml) induced by the treatment with sc FURO (10 mg/kg) -f CAP (5 mg/kg) was also increased after bilateral proglumide (50 ug/0.2 μl) injections into LPBN. CCK-8 (0.5 μg/0.2 μl) into LPBN reduced sc FURO + CAP induced 0.3 M NaCl intake for the first 30 minutes (0.5±0.3 vs 2.610.6 ml) after treatment. These results suggest that cholecystokinin levels in the LPBN may play an Inhibitory role in the control of sodium intake. Supported by NHLBIHL 14338, HL 44546, NASA NAGW-4358 and FAPESP 93/0167-8.